Efektivitas Prosedur Mediasi pada Perkara Gugat Cerai di Pengadilan Agama Serang Kelas 1a Berdasarkan Peraturan Mahkamah Agung Republik Indonesia Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan - Khairunisa, Annisa; Aslami, Iron Fajrul; Pramono, Aris Setyanto (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Based on Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures, there is a dispute resolution through a negotiation process to obtain an agreement between the Parties assisted by a Mediator. Based on the Mediation Procedure at the Serang Religious Court Class 1A, the effectiveness of the mediation procedure is influenced by internal factors from the quality of the mediator in handling the case and external factors from the defendant and plaintiff who have good intentions and understand the meaning of the purpose of the mediation procedure in court. This study aims to determine the legal basis governing mediation procedures in religious court procedural law at the Serang Class 1A Religious Court, identifying factors that influence the effectiveness of mediation procedures in divorce cases. This study employed a normative juridical legal research method. Data collection techniques included document and literature review, interviews with mediator judges, and secondary data analysis from the case information system (SIPP). This approach was chosen to obtain a comprehensive overview of the implementation of mediation procedures based on applicable regulations. The results of this study indicate that mediation procedures are clearly regulated in Supreme Court Regulation Number 1 of 2016, and information regarding these provisions can be accessed through the court's website. However, the absence of visual information media such as banners in the mediation room reduces the parties' understanding of the importance of the Mediation Procedure. The success of mediation is greatly influenced by the awareness and participation of the parties, the quality of the mediator's role in handling the case, and the support of facilities and infrastructure within the court environment. Based on the research results, it can be concluded that the effectiveness of the mediation procedure is highly dependent on the awareness factor and the participation of good faith of the plaintiff, defendant or husband and wife, the quality of the mediator's role in handling the mediation procedure case increases the effectiveness of the mediation procedure, the court system is expected to carry out regular supervision and evaluation of the implementation of the mediation procedure in order to increase the effectiveness of mediation in the Serang Class 1A Religious Court.